HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP TERHADAP PENCEGAHAN FOOD BORNE DISEASE PADA SISWA SEKOLAH DASAR - Dyah Suryani (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2020)
Food safety is an important public health problem because more and more cases are reported related to the consumption of unsafe food. Inadequate knowledge about food safety among consumers, especially children, can increase the risk of health problems related to food safety, especially foodborne illness. To prevent foodborne illness among children, behavior that ensures the safety of food purchased and consumed by students is an important factor. The purpose of this study was to determine the relationship between knowledge and attitudes with food borne disease prevention behavior in 4th and 5th grade students of Triwidadi Pajangan Bantul State Elementary School. This study was an observational study with a cross-sectional approach. The population in this study were students in grades 4 and 5 of the State Elementary School (SDN) Triwidadi Pajangan Bantul, totaling 35 students. Samples are taken in totality samples. Data was collected using a knowledge, attitude and behavior questionnaire. Data analysis using chi-square test. There is a relationship between knowledge about the causes and prevention of food borne disease with food borne disease prevention behavior (p value = 0.027) in 4th and 5th grade students of Triwidadi Bantul Pajangan Bantul. There is no relationship between attitudes about the causes and prevention of food borne disease with food borne disease prevention behavior (p value = 0.082) in 4th and 5th grade students of Triwidadi Bantul Pajangan Bantul. There is a relationship between knowledge and food borne disease prevention behavior and there is no relationship between attitude and food borne disease prevention behavior in 4th and 5th grade students of Triwidadi Bantul Pajangan Bantul.